Targeting the blood–brain barrier with phytochemicals to attenuate vascular cognitive impairment: mechanisms and therapeutic potential across etiologies - Jin, Zixiang; Zhai, Xianglong; Bai, Yingfei; Hu, Jun; Yu, Haolu; Sang, Jiajia; Wu, Minghua; Hao, Feng (Frontiers in Nutrition, 2026)
Vascular cognitive impairment (VCI), a cognitive disorder arising from cerebrovascular pathology, currently lacks effective targeted therapies. Dysfunction of the blood–brain barrier (BBB) represents a pivotal event in VCI pathogenesis, characterized by tight junction degradation, neuroinflammation, and oxidative stress. Phytochemicals—including polyphenols, flavonoids, and polysaccharides—demonstrate promising multi-target potential in ameliorating VCI by preserving BBB integrity, mitigating neuroinflammation and oxidative stress, exerting neuroprotective effects, and modulating the gut–brain axis. However, the clinical translation of these compounds is currently impeded by low bioavailability and limited BBB permeability. Prioritizing the development of targeted delivery systems is essential to enhance the therapeutic efficacy and clinical utility of phytochemicals in the prevention and treatment of VCI.